A relação tecnologia-consumidor: um estudo exploratório qualitativo sobre o perfil do consumidor de varejo omnichannel na cidade de Uberlândia - Aranda, Eduardo Pinheiro (2020)
The growth of omnichannel retail is causing that consumers to change their buying habits and behavior, and it is essential to understand factors about purchasing intent in the consumer's context. This research sought to explore the factors that influencing consumers to purchase from omnichannel companies, specifically in Uberlândia-MG city, through the perception of consumers themselves. For this, the exploratory research was designed and realized through five focus groups using a sample of 22 volunteers between 18 and 44 years old who had experience in omnichannel shopping. The interviews resulted in 4 hours and 27 minutes of recording, which transcribed generated 74 pages and which, analyzed, presented 10 themes on the purchase intentions and channels choice of consumers in relation to omnichannel shopping in Uberlândia city, namely: “ performance expectation "," effort expectation ", social influence", "facilitating conditions", "habit", "price", "situational factors", "anxiety", "perceived trust" and "need for interaction". The consumers who participated in the study stated that their expectation of buying from omnichannel companies was trust in the channel management and transport company (when it is not the same company), the clarity and quality of the information (such as product availability and stock information), the possibility of regretting the purchase, equal prices between the channels of the same company and especially the perfect integration between the channels. The results instigate new questions and reflections on the reasons for the apparent lack of integration between the channels, if this occurs only in the city studied, the reasons for this occurrence, whether there is a gap in the interpretation of companies that have declared themselves omnichannel about this concept, among others, which reiterates the complexity of the generalization of themes and concepts to verify consumers' purchase intentions in this context.